La aplicación de la política de educación inclusiva en relación con el autismo en la Unidad Educativa del Milenio Bernardo Valdivieso en el periodo académico 2022-2023 - Moreira Palacios, María Verónica (2024)
This research was carried out to analyze the effectiveness of the application of the implementation of the inclusive education policy with a particular focus on autism, at the UEMBV in Loja, during the 2022-2023 academic period as well as to propose strategies for its effective execution. The bibliographic method was used to examine both the academic literature on inclusive education and autism and the current legal regulations in Ecuador. Using the quantitative method, a structured survey was carried out aimed at parents, educators and DECE professionals. The results allowed to measure the perception and experiences of the participants regarding inclusive education and autism. Applying the qualitative method, interviews were conducted with teachers, DECE officials and parents of students with autism. The methodological approach with the Atlas.ti tool provided a solid analytical structure promoting a more complete interpretation of the data obtained. The results reveal that, despite the availability of virtual training opportunities for teachers, there is a crucial challenge in the practical application of the acquired knowledge, followed by the scarcity of specialized services and a high number of students per classroom, which limits the teaching effectiveness especially in the context of inclusive education. Likewise, the need is highlighted not only for teachers awareness and their role as teachers, but also the active and effective participation of the family of the student with autism which is of vital importance. In conclusion, the strategies proposed could strengthen the implementation of the inclusive education policy, highlighting the integration of virtual training with practical experiences in the classroom to improve teacher training. Additionally, the importance of addressing the lack of specialized services and the high student-to-classroom ratio is emphasized.